Planning Matrix Sebagai Upaya Peningkatan Mutu Pelayanan Rawat Inap di Rumah Sakit Umum Bhakti Rahayu Surabaya - Ika Avrianti (Universitas Airlangga, 2016)
Inpatient unit of Bhakti Rahayu Hospital as one potential revenue center for the hospital expected to be able to support an increas the income of the hospital. The issue of this research is the decrease trend of Bed Occupancy rate 48,96% with trend -15,79%.This research aims to increas the quality of inpatient services care in Bhakti Rahayu Hospital based on planning matrix. This research was in inpatient unit Bhakti Rahayu Hospital with an descriptive design cross sectional study of the 80 patients who are representing inpatient hospitalization were taken by simple random sampling. Data was collected by using questionnaires distributed to patients and analysed by quantitative methods arranged in the planning matrix table. The results showed that inpatient services quality has not met the standards of good service so that the service implementation need improvement and enhancement services primarily on aspects of the physical and human resources. The conclusions showed that to increase the quality of health care based on internal factors was very important. Physical aspects and human resources are the top priority to fix up.Keywords:services quality, planning matrix, inpatient unit